Enhancing Students' Religious Character through Strategic Planning of Extracurricular Activities - Evanuraeni; Mulyawan Safwandy Nugraha (Journal of Educational Management Research, 2026)
This study investigates the role of systematic planning in religious extracurricular activities at Islamic secondary schools in Indonesia, aiming to strengthen students' religious character. In response to the challenges posed by globalization and secular cultural penetration, Islamic education must develop not only intellectual abilities but also strong moral and spiritual foundations. The study employs a qualitative case study approach, focusing on one school with a robust religious extracurricular program. Data was collected through semi-structured interviews, non-participant observation, and document analysis. The findings reveal that structured planning, which includes needs analysis, program design, resource allocation, and evaluation, significantly improves student participation in religious activities, such as prayers, Qur'an study, and social-religious activities, leading to better discipline, manners, and social awareness. The research highlights the importance of involving students in the planning process, enhancing their sense of ownership and leadership. The study contributes to Islamic education management by offering a conceptual model for effective religious program planning, with implications for improving character education practices in schools. Future research should explore the applicability of the proposed model across various educational settings.